Introduction to risk and failures tools and methodologies - Stamatis, D.H (CRC Press, 2014)
Risk is everywhere, in everything we do. Realizing this fact, we all must try to understand this "risk" and if possible to minimize it. This book expands the conversation beyond failure mode and effects analysis (FMEA) techniques. While FMEA is indeed a powerful tool to forecast failures for both design and processes, it is missing methods for considering safety issues, catastrophic events, and their consequences. This new book focuses on risk and HAZOP as they relate to major catastrophic events, safety, and risk. Specifically it addresses the process and implementation as well as understanding the fundamentals of using a risk methodologyin a given organization for evaluating major safety and or catastrophic problems."--